Participation in Project Preparation : Lessons from World Bank-assisted Projects in India - Vedeld, Trond (Washington, DC: World Bank, 2013)
The study assesses the extent to which the India program, is meeting the Bank's objective of mainstreaming participatory approaches, in project preparation, and design. From a variety of social, and natural resource management sectors, ten projects were selected, appraised during 1990 and 1998, in which participation was an overall project objective. Key findings suggest that beneficiary participation was successful, contributing to participatory designs in many projects. Social assessments were used more often than before, while involvement of primary beneficiaries improved during the 1990s, reflecting a change in the ways of thinking of, both Bank staff, and Government officials. Participatory work improved significantly, showing a move from a focus on social mitigation of potentially adverse impacts, to proactive work, with broader operational frameworks for participation in project planning. Direct beneficiary participation, was less common in strategy, and policy formulation, but more common in formulating local-level project approaches, though the level of primary beneficiary participation, never went beyond information sharing, and consultation. However, there was an increased collaboration with primary stakeholders, and, capacity building, and empowerment did take place. The study stipulates the potential of beneficiaries is underutilized, and challenges participatory management, to improve processes so as to adapt to the social, and institutional context, and, to consider participation within a broader local capacity.